Un enfoque diferente de las técnicas de clustering para el estudio de epidemias - Casas Cardoso, Gladys (1999)
Classification of an outbreak with the category of epidemics requires that some epidemiological and statistical parameters, which have to be studied simultaneously, are satisfied; mathematical theory helps epidemiologists indetection of epidemics in cases when it is not evident. At the present time, these situations ares studied with slutering techniques, with the help of specialized software inthese topics. The present work aims to study these techniques and its imporvement with including risk factors. It is also presented an application with real data.